Theoretical analysis of bacterial efflux pumps inhibitors: Strategies in-search of competent molecules and develop next. (August 2020) - Ghosh, Akash; Roymahapatra, Gourisankar; Paul, Debarati; Mandal, Santi M.
Graphical abstract: Highlights: Twenty-six potent bacterial efflux pumps inhibitors (EPIs) are summarized here. All the EPIs were docked with efflux pumps from five different classes. Molecules were optimized and theoretically analyzed following density functional theory. Electrophilicity and ionization potential of the molecules are important criteria to be a good EPI. Cathinone is the most effective one that may interact with four types of efflux pumps. Abstract: Multi-drug resistance (MDR) bacteria pose a significant threat to our ability to effectively treat infections due to the development of several antibiotic resistant mechanisms. A major component in the development of the MDR phenotype in MDR bacteria is over expression of different-type of efflux pumps, which actively pump out antibacterial agents and biocides from the periplasm to the outside of the cell. Consequently, bacterial efflux pumps are an important target for developing novel antibacterial treatments. Potent efflux pump inhibitors (EPIs) could be used as adjunctive therapies that would increase the potency of existing antibiotics and decrease the emergence of MDR bacteria. Several potent inhibitors of efflux pumps have been reported which has been summarized here. All the natural and synthetic EPIs were optimized with Gaussian and Avogadro software. The optimized structures were docked with each class of efflux pumps and their bonding parameters were computed. The theoretical analyses were performed with density functional theory (DFT). Overall, computational study revealed a good trend of electrophilicity and ionization potential of the EPIs, the obtained average values are within in the range of 0.001414 AU ± 0.00032 and 0.208821 AU ± 0.015545, respectively. Interestingly, cathinone interacts with most of the efflux pumps among the tested inhibitors. The electrophilicity and ionization potential of cathinone are 0.00198 and 0.2388 AU, respectively. The study opens a new road for designing future-generation target-specific efflux pump inhibitors, as well as one molecule with multiple inhibition abilities.